2014
DOI: 10.1007/s10847-014-0413-7
|View full text |Cite
|
Sign up to set email alerts
|

Selective nitration of calix[4]arenes that easily gave inherently chiral calix[4]arenes

Abstract: Proximally dietherified calix[4]arene at lower rim was selectively nitrated to give mononitrocalix[4]arene, dinitrocalix[4] arene, and trinitrocalix[4]arene,respectively, under different reaction conditions. These three nitrocalix[4]arenes could be purified in good yield just by recrystallization, which provided a concise approach to inherently chiral calixarene. It was disclosed by crystal structure of trinitrocalix[4]arene that R-enantiomer and S-enantiomer of it could form a self-included dimer by NO 2 -HAr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The phenolic ring with free hydroxyl group was the most active in the reactions of electrophilic substitution. We were able to substitute regioselectively its para ‐position (position 5) with the bromine atom (NBS, CHCl 3 /acetone, 25 °C, 24 h), [25] the nitro group (HNO 3 (67 %)/MeCOOH(100 %), CH 2 Cl 2 , 0–5 °C, 30 min–1 h) [29] and the formyl group (Cl 2 CH−O−Me, TiCl 4 , CH 2 Cl 2 , 25 °C, 30 min–6 h) [30,31] . The corresponding bromo‐, nitro‐ and formyl‐calix[4] 2 a – c , f , g were isolated with high yields (75–98 %) (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The phenolic ring with free hydroxyl group was the most active in the reactions of electrophilic substitution. We were able to substitute regioselectively its para ‐position (position 5) with the bromine atom (NBS, CHCl 3 /acetone, 25 °C, 24 h), [25] the nitro group (HNO 3 (67 %)/MeCOOH(100 %), CH 2 Cl 2 , 0–5 °C, 30 min–1 h) [29] and the formyl group (Cl 2 CH−O−Me, TiCl 4 , CH 2 Cl 2 , 25 °C, 30 min–6 h) [30,31] . The corresponding bromo‐, nitro‐ and formyl‐calix[4] 2 a – c , f , g were isolated with high yields (75–98 %) (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Zheng has shown that careful control of the ipso-nitration conditions of ap roximal dipropoxy-tert-butylcalix [4]arene 7 can give either mono-nitro 18 or tri-nitro 19 ICC products which pleasingly are available through recrystallisation of the reaction mixture (Scheme 7). [44] Similarly,B aldini and Stefano have reported ar ather smart one-step disproportionation reactiono ft risformyl calix [4]arene 20 via an intramolecular Cannizzaror eaction (Scheme 8). [45] However,i nb oth these cases the enantiomersh ave not yet been reportedly resolved, but the racemic mixturesh ave been shown, by 1 HNMR spectroscopy, to have smallb ut discernible interactions with chiral amines.…”
Section: Upperand Lower-rim Functionalisationmentioning
confidence: 95%
“…Lastly, two recent reports have demonstrated serendipitous methods that may be further developed into upper‐rim modified ICCs. Zheng has shown that careful control of the ipso ‐nitration conditions of a proximal dipropoxy‐ tert‐ butylcalix[4]arene 7 can give either mono‐nitro 18 or tri‐nitro 19 ICC products which pleasingly are available through recrystallisation of the reaction mixture (Scheme ) . Similarly, Baldini and Stefano have reported a rather smart one‐step disproportionation reaction of trisformyl calix[4]arene 20 via an intramolecular Cannizzaro reaction (Scheme ) .…”
Section: Upper‐ and Lower‐rim Functionalisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable regioselective outcome of the aromatic electrophilic substitution reaction was unexpected as cage compound 1 contains several phenyl rings, which could also react with nitric acid, at least in principle. , It might be that the cage structure and the presence of the crown ether-like rings in 1 assist in the selective reaction of the reactive NO 2 + species with the side walls. To gain more insight into this possibility, 5 equiv of [NO 2 ]­BF 4 were added (at room temperature) to a solution of 1 in CDCl 3 .…”
mentioning
confidence: 99%